Critiquing the Development of Artificial Intelligence and Posthumanism: An Islamic Philosophical Perspective on Technology and the Future of Humanity - Moh Taufik R Yusuf; Ruslan (Postgraduate Program of the State Islamic Institute of Palopo, 2025)
The rapid advancement of Artificial Intelligence (AI) technologies has fundamentally transformed contemporary society while simultaneously intensifying debates surrounding posthumanism and the future of human existence. These developments raise profound philosophical questions regarding human identity, moral agency, and the ethical boundaries between humans and intelligent machines. This study critically examines the relationship between AI, posthumanism, and Islamic philosophy by employing qualitative library research grounded in philosophical hermeneutics, content analysis, and descriptive-critical interpretation. The findings indicate that although AI significantly contributes to scientific innovation and social development, it also introduces critical ethical challenges, including algorithmic bias, Explainable AI, AI Alignment, dehumanization, and the erosion of human moral responsibility. Unlike posthumanist perspectives that tend to blur the ontological distinction between humans and intelligent machines, Islamic philosophy affirms human beings as moral agents entrusted with the responsibility of stewardship (khalifah). As its principal theoretical contribution, this study proposes the Islamic Posthuman Ethics Framework (IPEF), which integrates tawhid as the ontological foundation, khalifah as the basis of moral agency, and maqasid al-shariah as the ethical framework for evaluating AI development. The proposed framework advances five operational principles—human dignity, justice, accountability, transparency, and public benefit—as normative foundations for Responsible AI Governance within the Islamic philosophical tradition.